The influential factors of the heritage shophouses’ architectural design in urban historic districts in Malaysia: a review / Mohd Amirul Hakim Zamri, Roshida Abdul Majid and Mohd Hisyam Rasyidi - Hakim Zamri, Mohd Amirul; Abdul Majid, Roshida; Rasyidi, Mohd Hisyam (Universiti Teknologi MARA, Perak, 2023)
Heritage shophouses are the primary architectural legacy that has greatly characterised the place identity of the urban historic district in Malaysia since the 17th century through its distinctive architectural design character. In contrast to the modern building design that is seen as contextually isolated from the place identity of the urban historic district, the architectural identity of heritage shophouses is seen as successful in fitting into the place identity due to its significantly responsive architectural identity to contextual factors. This paper aims to systematically review the influential factors on the Malaysian heritage shophouse design which constitutes its architectural identity through content analysis. This paper extracts scholars’ studies on heritage shophouse architectural design features, heritage shophouse morpho-typologies, and the factors that influence its architectural identity development. Heritage shophouses in Malaysia are morphologically categorized into Early Heritage Shophouse styles, Eclectic Heritage Shophouses, and Non-Cultural Heritage Shophouse styles. Regardless of their architectural styles, all heritage shophouses are characterized by the façade articulation, the interior design including the spatial organization system, and the building construction materials. Every element is primarily influenced by the tropical topographical climates and material sources as a basic architectural adaptation, the building development standards set by the colonial regimes, cultural assimilation, and the advancement of building construction and materials. The findings of this study can help architects how to prioritize design considerations in developing their new architectural intervention design ideas in the urban historic district to preserve its valuable historical characteristics.